1982
DOI: 10.1111/j.1365-3180.1982.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

The dormancy of wild oat seed (Avena fatua L.) from plants grown under various temperature and soil moisture conditions

Abstract: Summary Wild oat plants of types fA, fB and fC were grown at a constant 15 or 20°C during the period of seed maturation. Seed of the three types differed little in dormancy when grown at 15°C, but at 20°C a larger proportion of seeds of type fA were dormant compared with fB or fC. Overall, dormancy of seed produced at 15 and 20°C was 97 and 63% respectively. Plants of another collection of type fB were grown from seed at 15 or 20°C with or without water stress applied only from the time of panicle emergence. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 13 publications
5
43
2
1
Order By: Relevance
“…This is contrary to results found for members of the Poaceae, including Avena fatua (Peters, 1982), Sorghum halepense (Benech Arnold et al, 1992) and Bromus tectorum (Meyer and Figure 5. This is contrary to results found for members of the Poaceae, including Avena fatua (Peters, 1982), Sorghum halepense (Benech Arnold et al, 1992) and Bromus tectorum (Meyer and Figure 5.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This is contrary to results found for members of the Poaceae, including Avena fatua (Peters, 1982), Sorghum halepense (Benech Arnold et al, 1992) and Bromus tectorum (Meyer and Figure 5. This is contrary to results found for members of the Poaceae, including Avena fatua (Peters, 1982), Sorghum halepense (Benech Arnold et al, 1992) and Bromus tectorum (Meyer and Figure 5.…”
Section: Discussioncontrasting
confidence: 71%
“…Invasive weeds within Australia are no exception. It is often observed that maternal drought reduces PD, as seen in the herbaceous weed Sinapis arvensis (Brassicaceae) (Luzuriaga et al, 2005) and Avena fatua (Poaceae) (Peters, 1982). Limited soil moisture during seed development also causes variation in seed dormancy status, depending on the species and the dormancy mechanism(s) involved (Fenner, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Other grasses, such as annual ryegrass (Lolium rigidum Gaud.) and wild oats, respond similarly (Peters 1982b;Steadman et al 2004). It is possible that similar generalization may apply for junglerice and that the higher temperatures have masked any differences in dormancy brought on by drought stress.…”
Section: Resultsmentioning
confidence: 94%
“…This would account for the observation that seeds of stressed Avena fatua plants were found to have four times more (gibberellin-induced) a-amylase than seeds of unstressed plants (Peters, 1982b). This would account for the observation that seeds of stressed Avena fatua plants were found to have four times more (gibberellin-induced) a-amylase than seeds of unstressed plants (Peters, 1982b).…”
Section: Droughtmentioning
confidence: 90%
“…In Pennisetum typhoides there is very little effect of developmental temperature in the range 22-31 °C, but a marked decline in germinability in seeds developed at 19°C (Mohamed et al, 1985). Its dormancy was first shown to be reduced by higher temperatures during development by Sexsmith (1969), and the effect was confirmed in subsequent studies by Richardson (1979), Sawhney and Naylor (1980), Peters (1982b) and Somody et al (1984). Its dormancy was first shown to be reduced by higher temperatures during development by Sexsmith (1969), and the effect was confirmed in subsequent studies by Richardson (1979), Sawhney and Naylor (1980), Peters (1982b) and Somody et al (1984).…”
Section: Temperaturementioning
confidence: 93%